PENGARUH PARTISIPASI ANGGOTA, KUALITAS PENGELOLA, KUALITAS PENGURUS, DAN PERANAN PEMERINTAH TERHADAP KEBERHASILAN USAHA KOPERASI. (KASUS KUD DI KABUPATEN BULELENG BALI) - KETUT RANTAU (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
This research has been intended to find out the effects of memberparticipation, management guilty, and Government Roles on Cooperativesperformance, both the effect of the combination of those variables as well as theeffect of individual variables are observed. Path analysis is used intensively in thisstudy.This research was conducted in Buleleng regency, Cooperatives forsamples taken were there those who have been concussed as KUD’S Mandiri. Themembers of KUD’s taken ware (n = 950) and the KUD’s management staff ware(n = 65) taken from the KUD’s for samples based on the term of the proportionalallocation.Experiment using parth Analysis has show that, each of the variables(members Participation, the Management’s and of the Government’s roles) havepositive effect and significant on the performance of the KUD’s.